DISCLOSING MONETARY TERMS OF R&D ALLIANCES - Levitas, Edward; Singh, Sarthak; McFayden, M. Ann; Ahsan, Mujtaba (International Journal of Engineering Technologies and Management Research, 2024)
We investigate how biotechnology and pharmaceutical R&D alliances operating in an emerging and uncertain environment affects the partner’s decisions to provide unmandated alliance monetary terms. We identify factors promoting R&D alliance partners’ desire to disclose monetary arrangements, and factors compelling firms to conceal these arrangements. Voluntarily disclosed monetary arrangements of R&D alliances may impact the overall success of the alliance, partners’ performance independent of the alliance, and future R&D costs. Disclosure likely lowers the future cost of capital for certain partners, reducing future R&D costs; yet, disclosure may inadvertently provide proprietary information to competitors. Biotechs seek partnership with pharmaceuticals with established track records in getting drugs to market. Pharmaceuticals seek partnerships with biotechs possessing skills, (i.e. R&D research). We contend the biotech partner’s stock price uncertainty and near-term financial capital needs and the larger pharmaceutical firm’s market experience will impact the decision to disclose alliance monetary arrangements. We find support for our hypotheses using Probit regressions.